Development of the symbol system in consecutive interpreting - S. N. Kurbakova (Дискурс профессиональной коммуникации, 2019)
The work is aimed at systematizing knowledge on brief note-taking in consecutive interpreting and the prospects of its development for interpreting optimization. The author proceeds from the definition of note-taking in consecutive interpreting as a system of auxiliary means, external memory incentives which support the process of interpreting, and qualifies it not as an objective by itself but as a helpful instrument for interpreters, which enables them to more effectively record and reconstruct the information incorporated in the original text and then communicate it observing the translation language norms. Alongside this, when interpreting, a professional develops new sense coding symbols to record the information in a graphical form. The symbols used by the interpreter testify to what key data the interpreter focuses on and how this information is interpreted. An overview is given of the history and principles of note-taking in consecutive interpreting (those of economy, visualization and universality).The article makes the case that more active international contacts, broader areas of discussion call for further development of the system of note-taking in consecutive translation. As times are changing, new phenomena and concepts need new corresponding symbols for note-taking. For example, nowadays the spread of international terrorism is one of the greatest challenges for the global community. More and more attention is being paid to the methods of fighting terrorism and its origins, which is becoming a priority at many conferences and other international events with the issues of security and cooperation between different countries on the agenda. The article suggests a number of symbols to be used to interpret communication in the political and military spheres.In conclusion the author summarises the reasons why she considers the development of the symbol system in consecutive translation a topical and promising process, both theoretically and practically.